Impregnation liquid as well as preparation method and application thereof

By using impregnation liquid in the magnetic powder core, combined with soft magnetic alloy powder, different types of organic resins and reactive diluents, the pore problem of the magnetic powder core after high-temperature annealing is solved, its mechanical strength and magnetic properties are improved, and its hot and cold impact is achieved. Improved reliability in the environment.

CN119446754APending Publication Date: 2025-02-14HENGDIAN GRP DMEGC MAGNETICS CO LTD +1

Patent Information

Application Number
CN202411739768.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, pores appear in the magnetic powder core during high-temperature annealing process, reducing mechanical strength and reliability. At the same time, the organic solvent introduces new pores in the production process, affecting magnetic properties.

Method used

Using an impregnation liquid, the introduction of soft magnetic alloy powder, the first organic resin, the second organic resin and the reactive diluent act synergistically to improve the mechanical strength and magnetic properties of the magnetic powder core, and to improve reliability in a hot and cold impact environment.

Benefits of technology

Maintain the high magnetic permeability of the magnetic powder core, while improving the DC superposition characteristics and mechanical strength, enhancing reliability in hot and cold impact environments, and obtaining a magnetic powder core with excellent comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162360700000061
    Figure BDA0005162360700000061
  • Figure BDA0005162360700000111
    Figure BDA0005162360700000111
  • Figure BDA0005162360700000112
    Figure BDA0005162360700000112
Patent Text Reader

Abstract

The invention relates to an impregnation liquid as well as a preparation method and application thereof. The impregnation liquid comprises magnetically soft alloy powder, a binder and an active diluent, the binder comprises first organic resin and second organic resin; the first organic resin and the second organic resin are different in type. According to the impregnation liquid provided by the invention, the soft magnetic alloy powder, the first organic resin, the second organic resin and the reactive diluent are introduced, so that under the synergistic effect of the substances, the direct current superposition characteristic of the impregnated magnetic powder core is improved while the treated magnetic powder core still keeps relatively high magnetic conductivity; the mechanical strength of the magnetic powder core is enhanced, and the reliability of the magnetic powder core in a cold and hot shock environment is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic materials, and in particular to an impregnation liquid and a preparation method and application thereof. Background Art

[0002] Metal magnetic powder core, also known as soft magnetic composite material (SMC), is a powder material obtained by wrapping the surface of soft magnetic powder particles with insulating medium and pressing them into the desired shape using powder metallurgy process. It has excellent magnetic properties. In order to ensure that the powder has good molding ability, epoxy resin, silicone resin, phenolic resin and other resins are required as insulating binders. At the same time, internal stress is inevitably introduced during the molding process, which seriously affects the performance of the magnetic powder core. Therefore, in order to maintain a high magnetic permeability of the magnetic powder core, the molded magnetic powder core green body is currently treated at high temperature (550-750℃) to eliminate the influence of internal stress.

[0003] However, the high-temperature annealing process will cause the internal organic resin to decompose, resulting in a large number of pores inside, reducing the mechanical strength of the magnetic powder core and destroying the reliability of the magnetic powder core. Therefore, relevant researchers often use the impregnation process to infiltrate the impregnation liquid into the internal pores of the magnetic powder core, which can improve the mechanical strength and reliability of the magnetic powder core after curing. The organic resin and its additives in the impregnation liquid play a vital role in the mechanical strength and reliability of the magnetic powder core, and their usage will also have different degrees of influence on the magnetic properties of the magnetic powder core.

[0004] CN115966360A discloses an impregnation liquid and its application, a preparation method of a magnetic powder core and its application, wherein the impregnation liquid comprises ferrite powder, epoxy resin, curing agent, dispersant and diluent, and the mechanical strength of the magnetic powder core is improved by the impregnation liquid. However, organic solvents such as ethanol, toluene, acetone and xylene used in the prior art are prone to introduce new pores during the production process, and the magnetic powder core does not have strong reliability in a cold and hot shock environment.

[0005] CN112489918A discloses an alloy magnetic powder core and its preparation method and use, which uses a special coating compensation liquid to fill the internal pores caused by molding and sintering, thereby improving the performance and corrosion resistance of the magnetic powder core. However, due to the increase of non-magnetic substances inside the magnetic powder core, the magnetic permeability decreases and the DC superposition characteristics deteriorate.

[0006] CN118116712A discloses a metal magnetic powder core impregnation liquid and a preparation method thereof, wherein the impregnation liquid is composed of the following components and their weight ratios: 30-60 parts of epoxy resin; 30-60 parts of diluent; 3-30 parts of additives, which are used to reduce the curing shrinkage rate of the impregnation liquid, reduce the curing internal stress of the impregnation liquid, and at the same time can achieve the effect of reducing the loss change rate of the magnetic powder core after impregnation. However, inorganic additives are added in the prior art, which makes the risk of magnetic permeability attenuation exist, and the magnetic powder core treated with the impregnation liquid does not have strong reliability in a cold and hot shock environment.

[0007] In view of the defects existing in the above-mentioned prior art, providing an impregnation liquid that can effectively improve the performance of the magnetic powder core has become an urgent problem to be solved. Summary of the invention

[0008] In order to solve the above technical problems, the purpose of the present invention is to provide an impregnation liquid and a preparation method and application thereof. In the impregnation liquid provided by the present invention, by introducing soft magnetic alloy powder, a first organic resin, a second organic resin and an active diluent, under the synergistic effect of each substance, it can ensure that the treated magnetic powder core still maintains a high magnetic permeability, while improving the DC superposition characteristics of the magnetic powder core after impregnation, enhancing the mechanical strength of the magnetic powder core, and improving the reliability of the magnetic powder core in a cold and hot shock environment.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides an impregnation solution, the impregnation solution comprising soft magnetic alloy powder, a binder and an active diluent;

[0011] The binder includes a first organic resin and a second organic resin;

[0012] The first organic resin and the second organic resin are of different types.

[0013] In the impregnation liquid provided by the present invention, by introducing soft magnetic alloy powder, a first organic resin, a second organic resin and an active diluent, under the synergistic effect of each substance, the treated magnetic powder core can maintain a relatively high magnetic permeability, and the DC superposition characteristics of the treated magnetic powder core can be improved, and the mechanical strength of the magnetic powder core can be enhanced, so that the magnetic powder core can have strong reliability in cold and hot shocks, thereby obtaining a magnetic powder core with excellent comprehensive performance.

[0014] The present invention introduces soft magnetic alloy powder into the impregnation liquid, which can reduce the content of the binder, avoid introducing too much binder during the treatment of the magnetic powder core, and compensate for the magnetic permeability of the treated magnetic powder core and improve its DC superposition characteristics; adding a first organic resin and a second organic resin of different types and characteristics into the impregnation liquid, and using an active diluent, can make the impregnation liquid more easily penetrate into the interior of the magnetic powder core, and jointly improve the mechanical strength and magnetic properties of the magnetic powder core, and improve the reliability of the magnetic powder core in a cold and hot shock environment, wherein the addition of the active diluent replaces the organic solvent diluent in the prior art, and can avoid the generation of new pores caused by the volatilization of the organic solvent during the curing process of the magnetic powder core, thereby avoiding the decrease in the magnetic properties of the magnetic powder core, and ensuring that the magnetic powder core has strong reliability during the cold and hot shock process.

[0015] Preferably, the impregnation liquid comprises, by weight:

[0016] 10-30 parts of soft magnetic alloy powder;

[0017] 40-60 parts of binder;

[0018] Active diluent 7-40 parts.

[0019] In the present invention, in parts by weight, the mass fraction of the soft magnetic alloy powder is 10-30 parts, for example, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, etc.; the mass fraction of the binder is 40-60 parts, for example, 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts or 60 parts, etc.; the mass fraction of the active diluent is 7-40 parts, for example, 7 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or 40 parts, etc.

[0020] The present invention regulates the content of each substance in the impregnation liquid, can further improve the magnetic permeability stability and DC superposition characteristics of the impregnated magnetic powder core, enhance the mechanical strength of the magnetic powder core, and improve its reliability in a cold and hot shock environment, and further optimize the comprehensive performance of the treated magnetic powder core.

[0021] Among them, regulating the mass fraction of soft magnetic alloy powder in the impregnation liquid can compensate for the attenuation of the magnetic permeability of the magnetic powder core caused by the non-magnetic material inside it while ensuring the impregnation effect, and at the same time improve its DC superposition characteristics. If the amount of soft magnetic alloy powder added is too little, it will not be able to effectively compensate for the magnetic permeability of the magnetic powder core and improve the DC superposition characteristics, thereby causing the magnetic permeability and DC superposition characteristics of the treated magnetic powder core to deteriorate; if the amount of soft magnetic alloy powder added is too much, the overall penetration effect of the impregnation liquid will be worse, and the effects of curbing the attenuation of magnetic permeability, improving DC superposition characteristics, and improving mechanical strength and material reliability will be affected to a certain extent.

[0022] Regulating the mass fraction of the binder in the impregnation liquid can ensure the viscosity and impregnation penetration ability of the impregnation liquid while providing assistance for the magnetic powder core to obtain excellent mechanical strength and thermal shock reliability. Adding too much or too little binder will cause the treatment effect of the impregnation liquid on the magnetic powder core to deteriorate, thereby causing the performance of the treated magnetic powder core to deteriorate.

[0023] Adjusting the amount of active diluent added can help reduce the viscosity of the impregnation liquid and improve its penetration into the magnetic powder core. If the amount of active diluent added is too low, the viscosity of the impregnation liquid will be too high, and the impregnation effect on the internal pores of the magnetic powder core will be poor, affecting various performances. If the amount of active diluent added is too high, the proportion of other components in the impregnation liquid will be small, and the efficacy of other components cannot be fully exerted. At the same time, excessive introduction of active diluent will cause a certain degree of deterioration in the strength and reliability of the treated magnetic powder core.

[0024] Preferably, the soft magnetic alloy powder comprises nano iron-nickel powder.

[0025] The present invention selects nano iron-nickel powder as soft magnetic alloy powder and adds it into the impregnation liquid, which can further improve the magnetic permeability and direct current superposition characteristics of the processed magnetic powder core.

[0026] Preferably, the nickel content in the nano iron-nickel powder is 47-50wt%, such as 47wt%, 48wt%, 49wt% or 50wt%, and the iron content is 49-52wt%, such as 49wt%, 50wt%, 51wt% or 52wt%.

[0027] Preferably, the average particle size of the soft magnetic alloy powder is 20-50 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm or 60 nm.

[0028] The present invention regulates the average particle size of the soft magnetic alloy powder, can ensure that the soft magnetic alloy powder effectively penetrates into the interior of the magnetic powder core, and improves the magnetic permeability and DC superposition characteristics of the processed magnetic powder core.

[0029] Preferably, the reactive diluent comprises cresyl glycidyl ether and / or methacrylate glycidyl ether.

[0030] Preferably, the first organic resin includes bisphenol F type epoxy resin.

[0031] The first organic resin of the present invention adopts bisphenol F epoxy resin, which has the advantages of low viscosity and easy penetration into the interior of the magnetic powder core, and can ensure that more impregnation liquid penetrates into the interior of the magnetic powder core, thereby improving the treatment effect of the impregnation liquid on the magnetic powder core.

[0032] Preferably, the epoxy equivalent of the first organic resin is 140-180 g / eq, for example, 140 g / eq, 145 g / eq, 150 g / eq, 155 g / eq, 160 g / eq, 165 g / eq, 170 g / eq, 175 g / eq or 180 g / eq, etc.

[0033] Preferably, the viscosity of the first organic resin at room temperature is 2000-4000 cps, for example, 2200 cps, 2400 cps, 2600 cps, 2800 cps, 3000 cps, 3200 cps, 3400 cps, 3600 cps, 3800 cps or 4000 cps.

[0034] In the present invention, "room temperature" refers to a temperature of 25±5°C, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, etc.

[0035] Preferably, the second organic resin comprises liquid crystal epoxy resin.

[0036] Preferably, the second organic resin includes a liquid crystal epoxy resin containing a dimethylbiphenyl group.

[0037] The second organic resin in the present invention adopts a liquid crystal epoxy resin containing dimethylbiphenyl groups, which has the characteristics of high glass transition temperature, high modulus, high toughness and high thermal conductivity, and can make the magnetic powder core obtained after the impregnation liquid treatment have better magnetic permeability stability and stronger mechanical strength, thereby improving the reliability of the magnetic powder core in a cold and hot shock environment.

[0038] Preferably, the mass ratio of the first organic resin to the second organic resin is (2-5):1, such as 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, etc., preferably (3-4):1.

[0039] In the present invention, if the mass ratio of the first organic resin to the second organic resin is too small, and the amount of the first organic resin added is too small, the viscosity of the impregnation liquid will be too high, and the ability to penetrate into the internal pores of the magnetic powder core will be poor, affecting the impregnation effect, and further affecting the various properties of the treated magnetic powder core; if the mass ratio of the two is too large, and the amount of the second organic resin added is too small, the advantages of the liquid crystal epoxy resin itself, such as high glass transition temperature, high modulus, high toughness and high thermal conductivity, cannot be fully utilized, so that the mechanical strength and temperature resistance of the magnetic powder core after impregnation are greatly deteriorated.

[0040] Preferably, the impregnation liquid further comprises a curing agent and / or a dispersant, preferably a curing agent and a dispersant.

[0041] Preferably, when a curing agent and a dispersant are included, the impregnation liquid includes, by weight:

[0042]

[0043] In the present invention, in terms of weight parts, the mass parts of the curing agent are 9-15 parts, such as 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc.; the mass parts of the dispersant are 2-4 parts, such as 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts, etc.

[0044] Preferably, the curing agent includes any one of 4,4-diaminodiphenylmethane, diethyltoluenediamine or methylcyclohexanediamine, or a combination of at least two thereof.

[0045] Preferably, the dispersant comprises BYK-111 dispersant and / or AFCONA-5210 dispersant.

[0046] In a second aspect, the present invention provides a method for preparing the impregnation liquid according to the first aspect, the method for preparing the impregnation liquid comprising the following steps:

[0047] Mixing soft magnetic alloy powder, a binder and an active diluent to obtain the impregnation solution;

[0048] The binder includes a first organic resin and a second organic resin;

[0049] The first organic resin and the second organic resin are of different types.

[0050] The preparation method of the impregnation liquid provided by the present invention directly mixes the raw materials, has a simple preparation process, low cost and is easy to operate, and the obtained impregnation liquid contains soft magnetic alloy powder that can effectively compensate for the magnetic properties of the magnetic powder core; the first organic resin and the second organic resin of different types can play different roles and effects, and are combined with the active diluent to achieve excellent magnetic permeability stability of the magnetic powder core after impregnation liquid treatment, while jointly improving the mechanical strength and DC superposition characteristics of the treated magnetic powder core, and improving the reliability of the magnetic powder core in a cold and hot shock environment; in addition, the added active diluent replaces the organic solvent in the prior art, which can avoid the volatilization of the organic solvent in the magnetic powder core during the curing process to cause the formation of new pores, and further improve the comprehensive performance of the treated magnetic powder core.

[0051] Preferably, the specific process of the mixing includes: firstly mixing the binder and the active diluent for a first time, and then adding the soft magnetic alloy powder for a second mixing.

[0052] In the present invention, there is no specific limitation on the first mixing and the second mixing methods, which independently include but are not limited to mechanical stirring, manual stirring or ultrasonic dispersion, etc., and those skilled in the art can select them as needed.

[0053] Preferably, the soft magnetic alloy powder comprises nano iron-nickel powder.

[0054] Preferably, the first organic resin includes bisphenol F type epoxy resin.

[0055] Preferably, the second organic resin comprises liquid crystal epoxy resin.

[0056] Preferably, a curing agent and / or a dispersing agent, preferably a curing agent and a dispersing agent, are added during the first mixing process.

[0057] Preferably, the rotation speed of the first mixing is 80-120 r / min, for example, 80 r / min, 85 r / min, 90 r / min, 95 r / min, 100 r / min, 105 r / min, 110 r / min, 115 r / min or 120 r / min, etc.

[0058] Preferably, the first mixing time is 30-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.

[0059] Preferably, the second mixing speed is 30-50 r / min, such as 30 r / min, 35 r / min, 40 r / min, 45 r / min or 50 r / min.

[0060] Preferably, the second mixing time is 20-40 min, for example, 20 min, 25 min, 30 min, 35 min or 40 min.

[0061] In the present invention, if the second mixed product does not show stratification after standing, the preparation of the impregnation liquid is completed.

[0062] In a third aspect, the present invention provides a method for processing a magnetic powder core, the method comprising the following steps:

[0063] The impregnation liquid described in the first aspect is mixed with the magnetic powder core, and then solidified to obtain the treated magnetic powder core.

[0064] The present invention adopts a treatment process of mixing the magnetic powder core with a specific impregnation liquid and then solidifying it, which can ensure that the treated magnetic powder core has a high magnetic permeability stability, while also improving the DC superposition characteristics of the magnetic powder core, enhancing the mechanical strength of the magnetic powder core, and improving the reliability of the magnetic permeability in a cold and hot shock environment.

[0065] Preferably, the magnetic powder core includes any one of an AlSi magnetic powder core, an FeSi magnetic powder core, an FeSiCr magnetic powder core, an FeNi magnetic powder core, an amorphous magnetic powder core or a nanocrystalline magnetic powder core.

[0066] Preferably, the mixing time is 20-60 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.

[0067] Preferably, the mixing temperature is 20-30°C, such as 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, etc.

[0068] Preferably, the mixing method is: immersing the magnetic powder core in the impregnation liquid.

[0069] The present invention adopts the impregnation liquid to immerse the magnetic powder core under normal pressure.

[0070] Preferably, the curing includes a first curing stage, a second curing stage and a third curing stage.

[0071] The present invention adopts a continuous three-stage temperature rise curing process, which can avoid the negative influence of external temperature and reaction heat on the curing degree during the curing process. The first two curing stages are to ensure that the heat inside the magnetic powder core will not accumulate too high during the curing process and reach a higher degree of curing in this process. The third step of the curing process is to ensure that the impregnation liquid is cured after completion to ensure complete curing.

[0072] Preferably, the temperature of the first curing stage is 60-100°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.

[0073] Preferably, the first curing stage lasts for 0.5-2 hours, such as 0.5 hours, 1 hour, 1.5 hours or 2 hours.

[0074] Preferably, the temperature of the second curing stage is 110-130°C, such as 110°C, 115°C, 120°C, 125°C or 130°C, etc.;

[0075] Preferably, the second curing stage lasts for 0.5-2 hours, such as 0.5 hours, 1 hour, 1.5 hours or 2 hours.

[0076] Preferably, the temperature of the third curing stage is 180-220°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C or 220°C.

[0077] Preferably, the third curing stage lasts for 2-4 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0078] Compared with the prior art, the present invention has at least the following beneficial effects:

[0079] (1) In the impregnation solution provided by the present invention, by introducing soft magnetic alloy powder, a first organic resin, a second organic resin and an active diluent, under the synergistic effect of each substance, the magnetic powder core after treatment can be maintained to still have a high magnetic permeability, and the DC superposition characteristics of the magnetic powder core after treatment can be improved, and the mechanical strength of the magnetic powder core can be enhanced, so that the magnetic powder core can have strong reliability in cold and hot shocks, thereby obtaining a magnetic powder core with excellent comprehensive performance.

[0080] (2) The preparation method of the impregnation liquid provided by the present invention directly mixes the raw materials, and the preparation process is simple, low-cost and easy to operate. The impregnation liquid is made of soft magnetic alloy powder, a first organic resin and a second organic resin combined with an active diluent. The magnetic permeability stability of the magnetic powder core after the impregnation liquid treatment is excellent, while the mechanical strength and DC superposition characteristics of the treated magnetic powder core are improved, and the reliability of the magnetic powder core in a cold and hot shock environment is improved.

[0081] (3) The present invention adopts a treatment process of mixing the magnetic powder core with a specific impregnation liquid and then solidifying it, which can ensure that the treated magnetic powder core has a high magnetic permeability stability while also improving the DC superposition characteristics of the magnetic powder core, enhancing the mechanical strength of the magnetic powder core, and improving the reliability of the magnetic permeability under cold and hot shock environments. DETAILED DESCRIPTION

[0082] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0083] The bisphenol F epoxy resin used in the following examples is produced by Nan Ya Chemical Industry and its model is NPEF-170.

[0084] The BYK-111 dispersant used in the following examples is produced by BYK Chemicals of Germany.

[0085] The manufacturer of the AFCONA-5210 disperser used in the following examples is AFCONA Additives (Jiangsu) Co., Ltd.

[0086] The normal temperature and pressure mentioned in the following embodiments refer to a temperature of 25° C. and a pressure of 101 KPa.

[0087] The nano-iron-nickel powder used in the following examples has a nickel content of 49 wt % and an iron content of 51 wt %.

[0088] The liquid crystal epoxy resin containing dimethylbiphenyl groups used in the following examples is BMPE liquid crystal epoxy resin, and the structural formula of BMPE liquid crystal epoxy resin is as follows:

[0089]

[0090] Example 1

[0091] This embodiment provides an impregnation liquid, which includes, by weight:

[0092]

[0093] Among them, the average particle size of nano iron-nickel powder is 40nm; the binder is composed of bisphenol F epoxy resin and liquid crystal epoxy resin containing dimethyl biphenyl groups in a mass ratio of 3:1, the epoxy equivalent of bisphenol F epoxy resin is 160g / eq, and the viscosity at 25°C is 3000cps, and the liquid crystal epoxy resin containing dimethyl biphenyl groups is BMPE liquid crystal epoxy resin; the curing agent is 4,4-diaminodiphenylmethane; the dispersant is BYK-111 dispersant, and the active diluent is cresyl glycidyl ether.

[0094] This embodiment also provides a method for preparing the above-mentioned impregnation liquid, which specifically comprises the following steps:

[0095] (1) A binder, a 4,4-diaminodiphenylmethane curing agent, a BYK-111 dispersant, and a cresyl glycidyl ether active diluent were stirred in a mechanical stirrer for 40 minutes at a stirring speed of 100 r / min. The binder consisted of a bisphenol F epoxy resin and a BMPE liquid crystal epoxy resin in a mass ratio of 3:1 to obtain a mixed solution.

[0096] (2) Add nano-iron-nickel powder to the mixed solution obtained in step (1) according to the formula amount, and stir it in a mechanical stirrer for 30 minutes at a stirring speed of 40 r / min to obtain an impregnation solution.

[0097] This embodiment also provides a method for treating a magnetic powder core using the above-mentioned impregnation liquid, which specifically comprises the following steps:

[0098] The Sendust magnetic powder core (the main components of the magnetic powder core are: 8.5wt% Si, 5.5wt% Al, 86wt% Fe) is placed in the above-mentioned impregnation solution and soaked for 30 minutes at room temperature and pressure. Then, the soaked Sendust magnetic powder core is placed in an oven for curing, first at 80°C for 1 hour, then at 120°C for 1 hour, and finally at 200°C for 2 hours to complete the curing, thereby obtaining the treated magnetic powder core.

[0099] Example 2

[0100] This embodiment provides an impregnation liquid, which includes, by weight:

[0101]

[0102] Among them, the average particle size of nano iron-nickel powder is 20nm; the binder is composed of bisphenol F epoxy resin and liquid crystal epoxy resin containing dimethyl biphenyl groups in a mass ratio of 3:1, the epoxy equivalent of bisphenol F epoxy resin is 160g / eq, and the viscosity at 25°C is 3000cps, and the liquid crystal epoxy resin containing dimethyl biphenyl groups is BMPE liquid crystal epoxy resin; the curing agent is diethyltoluenediamine; the dispersant is BYK-111 dispersant, and the active diluent is cresyl glycidyl ether.

[0103] This embodiment also provides a method for preparing the above-mentioned impregnation liquid, which specifically comprises the following steps:

[0104] (1) A binder, a diethyltoluenediamine curing agent, a BYK-111 dispersant, and a cresyl glycidyl ether active diluent were stirred in a mechanical stirrer for 30 minutes at a stirring speed of 120 r / min. The binder consisted of a bisphenol F epoxy resin and a BMPE liquid crystal epoxy resin in a mass ratio of 3:1 to obtain a mixed solution.

[0105] (2) Adding nano-iron-nickel powder according to the formula amount to the mixed solution obtained in step (1), and stirring the mixed solution in a mechanical stirrer for 20 minutes at a stirring speed of 50 r / min to obtain an impregnation solution.

[0106] This embodiment also provides a method for treating a magnetic powder core using the above-mentioned impregnation liquid, which specifically comprises the following steps:

[0107] The iron silicon magnetic powder core (the main components of the magnetic powder core are: 6.5wt% Si, 93.5wt% Fe) is placed in the above-mentioned impregnation solution and soaked for 20 minutes at room temperature and pressure. Then, the soaked iron silicon magnetic powder core is placed in an oven for curing, first at 60°C for 2 hours, then at 110°C for 2 hours, and finally at 180°C for 4 hours to complete the curing, thereby obtaining the treated magnetic powder core.

[0108] Example 3

[0109] This embodiment provides an impregnation liquid, which includes, by weight:

[0110]

[0111] Among them, the average particle size of nano iron-nickel powder is 50nm; the binder is composed of bisphenol F epoxy resin and liquid crystal epoxy resin containing dimethyl biphenyl groups in a mass ratio of 3:1, the epoxy equivalent of bisphenol F epoxy resin is 160g / eq, and the viscosity at 25°C is 3000cps, and the liquid crystal epoxy resin containing dimethyl biphenyl groups is BMPE liquid crystal epoxy resin; the curing agent is 4,4-diaminodiphenylmethane; the dispersant is BYK-111 dispersant, and the active diluent is cresyl glycidyl ether.

[0112] This embodiment also provides a method for preparing the above-mentioned impregnation liquid, which specifically comprises the following steps:

[0113] (1) A binder, a 4,4-diaminodiphenylmethane curing agent, a BYK-111 dispersant, and a cresyl glycidyl ether active diluent were stirred in a mechanical stirrer for 60 minutes at a stirring speed of 80 r / min. The binder consisted of a bisphenol F epoxy resin and a BMPE liquid crystal epoxy resin in a mass ratio of 3:1 to obtain a mixed solution.

[0114] (2) Adding nano-iron-nickel powder according to the formula amount to the mixed solution obtained in step (1), and stirring for 40 minutes in a mechanical stirrer at a stirring speed of 30 r / min to obtain an impregnation solution.

[0115] This embodiment also provides a method for treating a magnetic powder core using the above-mentioned impregnation liquid, which specifically comprises the following steps:

[0116] An iron silicon chromium magnetic powder core (the main components of the magnetic powder core are: 3.5wt% Si, 4wt% Cr, 0.3wt% Ni, 92.2wt% Fe) is placed in the above-mentioned impregnation solution and soaked for 60 minutes at normal temperature and pressure. Then, the soaked iron silicon chromium magnetic powder core is placed in an oven for curing, first at 100°C for 0.5h, then at 130°C for 0.5h, and finally at 220°C for 3h to complete the curing, thereby obtaining the treated magnetic powder core.

[0117] Example 4

[0118] The difference between this embodiment and embodiment 1 is that in the impregnation liquid provided in this embodiment, the curing agent is methylcyclohexanediamine, the dispersant is AFCONA-5210, and the active diluent is glycidyl methacrylate. The rest of the contents are the same as those in embodiment 1.

[0119] Example 5

[0120] The difference between this embodiment and embodiment 1 is that in the impregnation solution provided in this embodiment, the binder is composed of bisphenol F epoxy resin and BMPE liquid crystal epoxy resin in a mass ratio of 5:1. The rest of the contents are the same as those in embodiment 1.

[0121] Example 6

[0122] The difference between this embodiment and embodiment 1 is that in the impregnation solution provided in this embodiment, the binder is composed of bisphenol F epoxy resin and BMPE liquid crystal epoxy resin in a mass ratio of 6:1. The rest of the contents are the same as those in embodiment 1.

[0123] Example 7

[0124] The difference between this embodiment and embodiment 1 is that in the impregnation solution provided in this embodiment, the binder is composed of bisphenol F epoxy resin and BMPE liquid crystal epoxy resin in a ratio of 1:1. The rest of the contents are the same as those in embodiment 1.

[0125] Example 8

[0126] The difference between this embodiment and embodiment 1 is that the impregnation liquid provided in this embodiment includes, by weight:

[0127]

[0128] The rest of the contents are the same as those in Example 1.

[0129] Example 9

[0130] The difference between this embodiment and embodiment 1 is that the impregnation liquid provided in this embodiment includes, by weight:

[0131]

[0132] The rest of the contents are the same as those in Example 1.

[0133] Example 10

[0134] The difference between this embodiment and embodiment 1 is that the impregnation liquid provided in this embodiment includes, by weight:

[0135]

[0136]

[0137] The rest of the contents are the same as those in Example 1.

[0138] Embodiment 11

[0139] The difference between this embodiment and embodiment 1 is that the impregnation liquid provided in this embodiment includes, by weight:

[0140]

[0141] The rest of the contents are the same as those in Example 1.

[0142] Example 12

[0143] The difference between this embodiment and embodiment 1 is that the impregnation liquid provided in this embodiment includes, by weight:

[0144]

[0145] The rest of the contents are the same as those in Example 1.

[0146] Embodiment 13

[0147] The difference between this embodiment and embodiment 1 is that in the impregnation liquid provided in this embodiment, bisphenol F epoxy resin is replaced by E44 epoxy resin. The rest of the contents are the same as those in embodiment 1.

[0148] Embodiment 14

[0149] The difference between this embodiment and embodiment 1 is that in the method for treating magnetic powder cores with impregnation liquid provided in this embodiment, the second curing stage is omitted, that is, the curing is completed by first keeping the temperature at 80°C for 1.5 hours and then keeping the temperature at 200°C for 2.5 hours. The rest of the contents are the same as those in embodiment 1.

[0150] Embodiment 15

[0151] The difference between this embodiment and embodiment 1 is that in the method for treating magnetic powder cores with impregnation liquid provided in this embodiment, the first curing stage and the second curing stage are omitted, that is, the curing is directly carried out by keeping the temperature at 200° C. for 4 hours. The rest of the contents are the same as those in embodiment 1.

[0152] Comparative Example 1

[0153] The difference between this comparative example and Example 1 is that in the impregnation solution provided in this comparative example, the binder omits the BMPE liquid crystal epoxy resin and is only a bisphenol F epoxy resin. The rest of the contents are the same as those in Example 1.

[0154] Comparative Example 2

[0155] The difference between this comparative example and Example 1 is that in the impregnation solution provided in this comparative example, the binder omits the bisphenol F epoxy resin and is only BMPE liquid crystal epoxy resin. The rest of the contents are the same as those in Example 1.

[0156] Comparative Example 3

[0157] The difference between this comparative example and Example 1 is that in the impregnation solution provided in this comparative example, the active diluent of cresyl glycidyl ether is replaced by an acetone organic solvent. The rest of the contents are the same as those in Example 1.

[0158] Comparative Example 4

[0159] The difference between this comparative example and Example 1 is that the nano-iron-nickel powder is omitted in the impregnation solution provided in this comparative example. The impregnation solution comprises, by weight:

[0160] 60 parts of adhesive;

[0161]

[0162] The rest of the contents are the same as those in Example 1.

[0163] The magnetic properties, mechanical strength and reliability of the magnetic powder cores of Examples 1-15 and Comparative Examples 1-4 before and after the impregnation liquid treatment were tested, and the test process is as follows:

[0164] (1) Magnetic properties test:

[0165] Ⅰ. Magnetic permeability test: The magnetic powder cores of Examples 1-15 and Comparative Examples 1-4 before and after treatment were tested for the real part μ' of magnetic permeability at 1 MHz using an Agilent E4991A analyzer, and the magnetic permeability change rate of the magnetic powder cores before and after treatment was calculated, that is, (magnetic permeability after treatment - magnetic permeability before treatment) / magnetic permeability before treatment × 100%. The test results are shown in Table 1.

[0166] Table 1

[0167]

[0168]

[0169] II. DC superposition characteristics (100Oe) test: The magnetic powder cores of Examples 1-15 and Comparative Examples 1-4 before and after treatment were uniformly wound with 30 turns of copper wire with a diameter of 0.4 mm to obtain a magnetic ring. The test conditions were 100kHz, 1V, and 25°C. The DC superposition characteristics of the magnetic ring under a magnetic field strength of 100Oe were calculated, and the DC superposition characteristics change rate of the magnetic powder cores before and after treatment was calculated, that is, (DC superposition characteristics after treatment - DC superposition characteristics before treatment) / DC superposition characteristics before treatment × 100%. The test results are shown in Table 2.

[0170] Table 2

[0171]

[0172] (2) Mechanical strength test: The strength of the magnetic powder cores of Examples 1-15 and Comparative Examples 1-4 before and after treatment was tested using a JSV-500D strength tester, and the magnitude of the force when the magnetic powder core broke was recorded, which was the mechanical strength of the magnetic powder core. The change rate of the mechanical strength of the magnetic powder core before and after treatment was calculated, that is, (mechanical strength after treatment - mechanical strength before treatment) / mechanical strength before treatment × 100%. The test results are shown in Table 3.

[0173] (3) Reliability test of thermal shock: The magnetic powder cores of Examples 1-15 and Comparative Examples 1-4 before and after treatment were subjected to 200 cycles at (-55)°C-125°C. The magnetic permeability of the magnetic powder cores before the cycles and after the 200 cycles were compared, and the attenuation degree was calculated as (magnetic permeability after the cycles - magnetic permeability before the cycles) / magnetic permeability before the cycles × 100%. The test results are shown in Table 3.

[0174] Table 3

[0175]

[0176] The test results show that:

[0177] (1) It can be seen from Examples 1 to 5 that in the impregnation liquid provided by the present invention, under the synergistic effect of various substances, the magnetic permeability stability of the treated magnetic powder core can be maintained at a relatively good level, while the DC superposition characteristics of the magnetic powder core after impregnation are improved, the mechanical strength of the magnetic powder core is enhanced, and the reliability of the magnetic powder core in a cold and hot shock environment is improved.

[0178] (2) By comparing Example 1 with Examples 6-7, it can be seen that if the mass ratio of the first organic resin to the second organic resin is too large and the amount of the second organic resin added is too small, the advantages of the liquid crystal epoxy resin itself, such as high glass transition temperature, high modulus, high toughness and high thermal conductivity, cannot be fully utilized, resulting in a significant deterioration in the strength and temperature resistance of the magnetic powder core after impregnation. If the mass ratio of the two is too small and the amount of the first organic resin added is too small, the overall viscosity of the impregnation liquid is high, which is not conducive to the penetration of various components into the internal pores of the magnetic powder core, resulting in different degrees of deterioration in the various properties of the treated magnetic powder core.

[0179] (3) By comparing Example 1 with Examples 8-9, it can be seen that when the content of the binder in the impregnation solution of the present invention exceeds a reasonable range, the effect of the impregnation solution will be greatly reduced, thereby causing various properties of the magnetic powder core treated therewith to be significantly deteriorated.

[0180] (4) By comparing Example 1 with Examples 10-11, it can be seen that in the impregnation solution of the present invention, if the amount of soft magnetic alloy powder added is too little, the ability of the nano-iron-nickel powder to compensate for the magnetic permeability and improve the DC superposition characteristics is insufficient, resulting in a significant deterioration in these two properties of the treated magnetic powder core; if the amount of soft magnetic alloy powder added is too much, the excessive amount of nano-iron-nickel powder will cause the overall penetration effect of the impregnation solution to deteriorate, and the improvement of the DC superposition characteristics and the improvement of strength and reliability will be affected to a certain extent.

[0181] (5) By comparing Example 1 and Example 12, it can be seen that in the impregnation solution of the present invention, if the amount of active diluent added is too low, the impregnation effect of the impregnation solution on the magnetic powder core will be poor, so that the various properties of the treated magnetic powder core will be affected.

[0182] (6) By comparing Example 1 with Example 13, it can be seen that in the impregnation liquid of the present invention, if the bisphenol F epoxy resin in the binder is replaced with E44 epoxy resin, the overall viscosity of the impregnation liquid will increase, affecting the penetration of the impregnation liquid into the internal pores of the magnetic powder core. At the same time, the interaction effect with the liquid crystal epoxy resin will also deteriorate, ultimately causing the various properties of the treated magnetic powder core to deteriorate to varying degrees.

[0183] (7) By comparing Example 1 with Examples 14-15, it can be seen that in the process of treating the magnetic powder core with the impregnation liquid of the present invention, if the second curing stage is omitted, the heat released during the curing reaction will have a negative impact on the entire curing process, thereby affecting the performance of the magnetic powder core after impregnation; if both the first curing stage and the second curing stage are omitted and the curing is directly performed at a higher temperature, the external high temperature and the heat generated during the reaction cannot be quickly released from the inside of the magnetic powder core, resulting in the performance of the resin in the binder being affected or even partially decomposed, ultimately resulting in the deterioration of the performance of the magnetic powder core.

[0184] (8) By comparing Example 1 with Comparative Example 1, it can be seen that the impregnation liquid of the present invention lacks liquid crystal epoxy resin and only uses bisphenol F epoxy resin. The bisphenol F epoxy resin has low viscosity, which can make the impregnation liquid easily penetrate into the interior of the magnetic powder core, so that the impregnation effect is good, the degree of decrease in the magnetic permeability of the magnetic powder core is relatively low, and the DC superposition characteristics are better than other comparative examples. However, due to the lack of addition of liquid crystal epoxy resin with high glass transition temperature, high modulus, high toughness and high thermal conductivity, the mechanical strength and resistance to cold and hot shock of the magnetic powder core after impregnation will be significantly deteriorated.

[0185] (9) By comparing Example 1 with Comparative Example 2, it can be seen that the impregnation liquid of the present invention lacks bisphenol F epoxy resin, which makes the impregnation effect of the impregnation liquid worse and leads to the problem of insufficient magnetic permeability compensation ability. Although liquid crystal epoxy resin has the advantages of high glass transition temperature, high modulus, high toughness and high thermal conductivity, it still needs to be matched with bisphenol F epoxy resin to obtain more excellent performance. This also means that it does not have relatively excellent capabilities in DC superposition characteristics, mechanical strength and thermal shock when used alone.

[0186] (10) By comparing Example 1 with Comparative Example 3, it can be seen that the present invention replaces the active diluent used in the impregnation liquid with acetone. Due to the volatility of acetone during use, secondary pores are easily generated in the magnetic powder core during the impregnation and curing process, resulting in deterioration of various performances of the treated magnetic powder core.

[0187] (11) By comparing Example 1 with Comparative Example 4, it can be seen that the present invention introduces soft magnetic alloy powder into the impregnation solution, which can reduce the content of the binder, avoid the introduction of too much binder during the magnetic powder core processing, compensate for the magnetic permeability of the treated magnetic powder core, and improve its DC superposition characteristics. If the soft magnetic alloy powder is lacking, the magnetic permeability of the treated magnetic powder core will be significantly reduced.

[0188] In summary, in the impregnation liquid provided by the present invention, under the synergistic effect of specific substances, the high magnetic permeability of the treated magnetic powder core can be maintained, while the DC superposition characteristics of the treated magnetic powder core can be improved, and the mechanical strength of the magnetic powder core can be enhanced, so that the magnetic powder core can have strong reliability in hot and cold shocks, thereby obtaining a magnetic powder core with excellent comprehensive performance.

[0189] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An impregnation liquid, characterized in that: The impregnation liquid comprises soft magnetic alloy powder, a binder and an active diluent; The binder includes a first organic resin and a second organic resin; The first organic resin and the second organic resin are of different types.

2. The impregnation liquid according to claim 1, characterized in that In parts by weight, the impregnation liquid comprises: 10-30 parts of soft magnetic alloy powder; 40-60 parts of binder; Active diluent 7-40 parts.

3. The impregnation liquid according to claim 1 or 2, characterized in that: The soft magnetic alloy powder includes nano iron-nickel powder; Preferably, the nickel content in the nano iron-nickel powder is 47-50wt%, and the iron content is 49-52wt%; Preferably, the average particle size of the soft magnetic alloy powder is 20-50 nm; Preferably, the reactive diluent comprises cresyl glycidyl ether and / or methacrylate glycidyl ether.

4. The impregnation liquid according to any one of claims 1 to 3, characterized in that: The first organic resin includes bisphenol F type epoxy resin; Preferably, the epoxy equivalent of the first organic resin is 140-180 g / eq; Preferably, the viscosity of the first organic resin at room temperature is 2000-4000 cps; Preferably, the second organic resin comprises liquid crystal epoxy resin; Preferably, the second organic resin comprises a liquid crystal epoxy resin containing a dimethylbiphenyl group; Preferably, the mass ratio of the first organic resin to the second organic resin is (2-5):1, preferably (3-4):

1.

5. The impregnation liquid according to any one of claims 1 to 4, characterized in that: The impregnation liquid further comprises a curing agent and / or a dispersant, preferably a curing agent and a dispersant; Preferably, when a curing agent and a dispersant are included, the impregnation liquid includes, by weight: Preferably, the curing agent includes any one of 4,4-diaminodiphenylmethane, diethyltoluenediamine or methylcyclohexanediamine, or a combination of at least two thereof.

6. A method for preparing an impregnation liquid according to any one of claims 1 to 5, characterized in that: The preparation method of the impregnation liquid comprises the following steps: Mixing soft magnetic alloy powder, a binder and an active diluent to obtain the impregnation solution; The binder includes a first organic resin and a second organic resin; The first organic resin and the second organic resin are of different types.

7. The method for preparing the impregnation liquid according to claim 6, characterized in that: The specific process of the mixing includes: firstly mixing the binder and the active diluent, and then adding the soft magnetic alloy powder for second mixing; Preferably, the soft magnetic alloy powder comprises nano iron-nickel powder; Preferably, the first organic resin comprises bisphenol F type epoxy resin; Preferably, the second organic resin comprises liquid crystal epoxy resin; Preferably, a curing agent and / or a dispersant are also added during the first mixing process, preferably a curing agent and a dispersant; Preferably, the first mixing speed is 80-120r / min; Preferably, the first mixing time is 30-60 min; Preferably, the second mixing speed is 30-50r / min; Preferably, the second mixing time is 20-40 min.

8. A method for processing a magnetic powder core, characterized in that: The method for processing the magnetic powder core comprises the following steps: The impregnation liquid according to any one of claims 1 to 5 is mixed with a magnetic powder core and then solidified to obtain the treated magnetic powder core.

9. The method for processing a magnetic powder core according to claim 8, characterized in that: The magnetic powder core includes any one of an aluminum-iron-silicon magnetic powder core, an iron-silicon magnetic powder core, an iron-silicon-chromium magnetic powder core, an iron-nickel magnetic powder, an amorphous magnetic powder core or a nanocrystalline magnetic powder core; Preferably, the mixing time is 20-60 min; Preferably, the mixing temperature is 20-30°C; Preferably, the mixing method is: immersing the magnetic powder core in the impregnation liquid.

10. The method for processing a magnetic powder core according to claim 8 or 9, characterized in that: The curing includes a first curing stage, a second curing stage and a third curing stage; Preferably, the temperature of the first curing stage is 60-100°C; Preferably, the first curing stage lasts for 0.5-2 hours; Preferably, the temperature of the second curing stage is 110-130°C; Preferably, the second curing stage lasts for 0.5-2 hours; Preferably, the temperature of the third curing stage is 180-220°C; Preferably, the third curing stage lasts for 2-4 hours.

Citation Information

Patent Citations

  • Alloy magnetic powder core and preparation method and application thereof

    CN112489918A

  • Metal magnetic powder core impregnation liquid and preparation method thereof

    CN118116712A

Cited By

  • Soft magnetic composite material and preparation method and application thereof

    CN120895354A